Agriculture, irrigation and drought induced international migration: Evidence from Mexico. (July 2022) - Fishman, Ram; Li, Shan
Highlights: Droughts increase migration rates from Mexico the U.S. The increase is stronger where agricultural production is more vulnerable to drought. Farmers are more likely to migrate during drought than non-farmers. This supports the hypothesis of an agricultural link between climate and migration Irrigation and non-farm enterprises reduce the tendency to migrate during drought. Abstract: There is now substantial empirical evidence that climatic variability increases international migration, but relatively little is known about the mechanism driving the association and about adaptations that may reduce it. We use detailed data on migrants from Mexico to the U.S. to provide evidence in support of the hypothesis that drought induced migration from Mexico to the U.S. is mediated by agricultural income shocks. Migration rates increase in drought years, but only in Mexico's drier regions, and the response is stronger in states and seasons in which agricultural production is also more sensitive to precipitation. Moreover, among the sample, only farmers display a significant increase in migration rates in drought years, and the effect is substantially weaker for households with access to irrigation.